The Effect of Liquid Organic Fertilizer and Urea Fertilizer on the Growth and Yield Swiss Chard - Panunggul, Victor Bintang Panunggul (Politeknik Pertanian Negeri Samarinda, 2024)
The purpose of this study is to ascertain how urea and liquid organic fertilizers affect the production and growth of swiss chard plants. A factorial Randomized Block Design (RAK) including two components with three replications was the research design. The dosage of liquid organic fertilizer, which comes in three levels: no treatment (P0), 30 mL (P1), and 50 mL (P2), is the first factor. Second, there are two amounts of urea fertilizer (U): control (U0), 15 g (U1), and 30 g (U2). The plant height, number of leaves, and leaf area are examples of the observed observation factors. On the other hand, the dry weight of the canopy, the dry root weight, and the fresh root weight are the yield variables. If the analysis of variance results show a significant and actual effect, additional test analysis utilizing Duncan's Multiple Range Test (DMRT) at the 5% level can be utilized to determine and observe the changes in treatment outcomes. The application of organic liquid fertilizer has no discernible impact on the development and productivity of swiss chard plants, according to the study's findings. At 50 mL, liquid organic fertilizer treatment does, however, actually affect the weight of the new plants. With the exception of the urea dosage on the variable fresh weight of the best plants in the treatment of 30 g of 23.88 g, urea fertilizer administration has a noticeable impact on plant growth. There is a noticeable difference in plant development when urea fertilizer is applied. The urea treatment has a major impact on Swiss chard plant output as well. The growth and output of Swiss chard plants are unaffected by the amount of urea fertilizer applied or the application of liquid organic fertilizer. Keywords: Liquid organic fertilizer, swiss chard, urea doses